The role of GeoGebra software in conceptual understanding and engagement among secondary school student - Hidayat, Riyan; Wan Mohd Noor, Wan Nurazlina; Nasir, Nurihan; Mohd Ayub, Ahmad Fauzi (STKIP Siliwangi Bandung (IKIP Siliwangi), 2024)
This study aims to identify the impact of GeoGebra software on conceptual understanding and engagement in the topic of Functions and Quadratic Equations in One Variable in high school. The study was conducted in a quasi-experimental design with 60 students at a secondary school in Muallim district. The study results were analyzed using descriptive statistics, inference, and the Pearson Correlation. Descriptive analysis indicates that students have a strong grasp of the topic taught, particularly showing high conceptual understanding and maximum engagement in interactive activities. Inference statistics reveal a significant difference in conceptual understanding levels between the treatment and control groups among Level Four students regarding Quadratic Functions and Equations in a Variable. In addition, there were significant differences in student engagement between the treatment and control groups. There is a significant relationship between the level of student engagement and students’ conceptual understanding of Quadratic Functions and Equations in One Variable for both groups. In conclusion, using GeoGebra software has an impact on the relationship between understanding the concept and involving students in learning the topic of Quadratic Functions and Equations in a Variable. © 2024, STKIP Siliwangi Bandung (IKIP Siliwangi). All rights reserved.